2007
DOI: 10.1093/annonc/mdm112
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of selective outpatient management of high-risk acute myelogenous leukemia on the incidence of septicemia

Abstract: Background: Curative intent chemotherapy for acute myelogenous leukemia (AML) leads to prolonged severe neutropenia, during which patients are highly susceptible to infection. Traditionally these high-risk patients were treated as inpatients. Our center recently implemented a selective ambulatory management policy for AML patients undergoing chemotherapy. Materials and methods:A retrospective analysis was conducted to assess the occurrence of septicemia in AML patients treated over a 5 years period with curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 24 publications
4
38
2
2
Order By: Relevance
“…Patients were discharged on levofloxacin, fluconazole, and acyclovir (or similar medications) and continued until ANC was 0.5¥10 9 or over. Patients were seen by an outpatient oncology nurse three times per week and by a physician once weekly.…”
Section: Outpatient Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were discharged on levofloxacin, fluconazole, and acyclovir (or similar medications) and continued until ANC was 0.5¥10 9 or over. Patients were seen by an outpatient oncology nurse three times per week and by a physician once weekly.…”
Section: Outpatient Managementmentioning
confidence: 99%
“…Patients were seen by an outpatient oncology nurse three times per week and by a physician once weekly. Transfusion thresholds in asymptomatic patients were: hematocrit less than 26% and platelet count less than 10¥10 9 . Patients with febrile neutropenia were hospitalized for intravenous antibiotics.…”
Section: Outpatient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…These infections require intravenous broad‐spectrum antibiotics 1, 4, 6, 10, as well as antibiotic prophylaxis (AP) during neutropenia, which has been shown to improve infection prevention and overall survival 2. Non‐randomized studies show that treatment of acute leukemia can be performed on an outpatient basis, allowing the patient to remain at home while under supervision in the active treatment phase and neutropenia period 11, 12, 13, 14, 15, 16, 17, 18, 19. Though feasible and safe, findings from our outpatient management study for acute leukemia showed that neutropenic fever followed by septicemia and pneumonia are the dominant causes of readmission during outpatient management 20.…”
Section: Introductionmentioning
confidence: 99%
“…Ambulatory care has been well described for patients who have undergone autologous hematopoietic stem cell transplant or allogeneic non-myeloablative hematopoietic stem cell transplant, as well as patients with acute leukemia who are discharged before neutrophil recovery and patients receiving treatment for high-risk febrile neutropenia. [3][4][5][6] The outpatient program provides care to both patients with high-risk febrile neutropenia and patients with non-neutropenic immunocompromised states.…”
mentioning
confidence: 99%